Village Based Seed Banks in Andhra Pradesh: a Case Study - Ch. Ravinder Reddy,; Vilas A Tonapi,; PG Bezkorowajnyj,; G. Thirupati Reddy,; SP Wani, (Journal of Agricultural Extension Management, 2025)
The great majorities of the world's food crops are annual species for which seed must be sown each season to establish a new crop. Consequently, seeds are the fundamental biological component of agricultural production. Agriculture in India is over 5000 years old. Farmers have been breeding, selecting and collecting enough seeds, all these years to meet their requirement. The very survival of Indian agriculture for centuries is a testimony to the sound wisdom on seed production and storage being nurtured by the agrarian community. These systems have been variously called a farmer-managed seed system (Bal and Douglas, 1992); Informal seed system (Cromwell et al 1992), traditional seed system and local seed system (Almekinders et al., 1994). But, constant rising population increased pressure on food grain production, is a great task before the agricultural scientists to achieve. In order to achieve the projected demand, quality seed of improved cultivars is the pre-requisite. Improved seed is a catalyst for making other inputs cost-effective. In spite of many efforts, seed supply particularly of food grain crops is a serious concern till today. More than 80% of crops in developing countries are sown from seed stocks selected and saved by farmers across developing countries (Osborne and Faye 1991; Jaffe and Srivastava 1992; Almekinders et al. 1994) and Banerjee (1984) stated that more than 85 percent of total seed sown in India is produced by farmers. In Semi-arid tropics of Andhra Pradesh, 80% of food-feed crops seed is from farmers own saved seed (Ravinder Reddy et al. 2007). Quality seed availability is only 12 percent of the total seed used for sowing each year. Hence, large area under food grain crops is still sown with seeds saved by farmers. Experimental evidence is there that cereal crops give 10-20 percent less yield per ha when farmers use their own saved seed. With simple calculation, one could say that about 20-30 million tones food grain production may be added in our total production through the use of quality seed of improved varieties and hybrids